POLYMERIC NANOPARTICLES: A PROMISING TOOL FOR THE TREATMENT OF DYSLIPIDEMIA - Muhmmad Yahya Qureshi; Ravi Sharma; Ashish Gupta; Pravin Kumar Sharma; G.N. Darwhekar (Current Research in Pharmaceutical Sciences, 2024)
Polymeric nanoparticles (NPs) are a promising platform for drug delivery in various biomedical applications. These nanoparticles, ranging from 1 to 1000 nm, can contain active substances either surface-adsorbed onto the polymeric core or trapped inside it. Both nanocapsules and nanospheres, which are identified by their morphological structures, are referred to as nanoparticles. They are typically fabricated from biocompatible and biodegradable polymers like polylactic-co-glycolic acid (PLGA), chitosan, or PEG. The synthesis of polymeric nanoparticles involves techniques like solvent evaporation, emulsification/solvent diffusion, the inotropic gelation method, emulsification/reverse salting-out, and nanoprecipitation, allowing precise control over particle size, shape, and drug-loading capacity. Surface modifications with targeting ligands or stimulus-responsive moieties can enhance therapeutic efficacy while minimizing off-target effects. Polymeric nanoparticles offer advantages over conventional drug delivery systems, including prolonged circulation times, sustained drug release kinetics, and protection of encapsulated drugs from degradation. Dyslipidemia, characterized by abnormal lipid levels in the bloodstream, is a major risk factor for cardiovascular diseases. They offer a controlled and targeted delivery platform for simvastatin, a lipid-lowering agent, which faces challenges such as poor solubility and limited bioavailability. Review articles state that polymeric nanoparticles are loaded with simvastatin, highlighting their potential benefits in improving drug stability, solubility, and bioavailability. Review articles highlighted that In vitro studies showed sustained release of simvastatin over an extended period and minimal cytotoxicity to cells, In vivo pharmacokinetic and pharmacodynamic studies in animal models of dyslipidemia revealed enhanced drug bioavailability and lipid-lowering efficacy compared to free simvastatin.